An integrated approach to understanding the sorption mechanism of phenanthrene by cork. - Olivella, M. À; Jové, P.; Bianchi, A.; Bazzicalupi, C.; Cano, L. (Chemosphere, 2012)
Previous studies have shown the high sorption affinity of polycyclic aromatic hydrocarbons by cork. The aim of the present work is to go further by investigating the sorption mechanism of polycyclic aromatic hydrocarbons (exemplified by phenanthrene) on cork and the availability of the chemical components (i.e. lignin, suberin, holocellulose and extractives) to retain phenanthrene. Two approaches were integrated to reach this objective: (1) statistical multivariate analysis to obtain correlations between the sorption capacity, measured as K(oc), and the sorbent properties (i.e. polarity, acidic functional groups, %dichloromethane extractives, %ethanol and water extractives, %suberin, %lignin and %holocellulose) and (2) modeling calculations to obtain information on interaction at the molecular level. The statistical multivariate analysis demonstrated a strong and positive correlation between K(oc) and the lignin content as well as negative correlations between K(oc) and the phenolic groups and %dichloromethane extractives contents. The modeling study showed that the lignin-phenanthrene interaction is mostly hydrophobic in nature being largely determined by the π-stacking interaction between the aromatic groups of the interacting partners. This result justifies the observed correlations as dichloromethane extractives, being hydrophobic, compete with phenanthrene adsorption, whereas phenolic groups, as well as negatively charged groups, enhance the hydrophilic character of the sorbent surface, thus hindering the adsorption of phenanthrene.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 23149185
Keywords: Biopolymer; Biosorption; Lignin; PAHs; p–p Interactions; suberin